Motivating employees in agile teams - Wdowiak, Anna (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
Nowadays enterprises confront the challenges of growing expectations of the market. High level of competition, turbulent business environment, it force on organizations flexible approach for customers, as well as the high level of the creativity and innovations. Employees also have higher expectations, they need to feel the usability of projects, have the influence on product, as well as the flexibility. The work on projects is transforming, current trends point to importance of agile methodologies in the process of the project management. In the implementation of projects in agile methodology, the key to success are employees, who are motivated to the performance of tasks. Creating the involved teams based on the flexibility, creativities and adaptability is a challenge for the organization. The concepts were analysed in the chapter: the agile management, motivating and motivation. The mail purpose of the chapter is finding the answer to the question, how to motivate employees in agile teams.